The expression and binding properties of the rice WRKY68 protein in the Xa21-mediated resistance response to Xanthomonas oryzae pv. Oryzae - Shuo YANG; Liang ZHOU; Liu-yang MIAO; Jia-nan SHI; Cai-qiang SUN; Wei FAN; Jin-ping LAN; Hao CHEN; Li-juan LIU; Shi-juan DOU; Guo-zhen LIU; Li-yun LI (Journal of Integrative Agriculture, 2016)
Plant WRKY transcription factors are involved in various physiological processes, including biotic and abiotic stress responses, as well as developmental processes. In this study, the expression patterns of the WRKY68 protein during interactions between rice 4021 containing the bacterial blight resistance gene Xa21 and Xanthomonas oryzae pv. oryzae (Xoo) were investigated. A possible modified form of the WRKY68 protein appeared in the Xa21-mediated disease resistance response, and its expression levels were similar in compatible and incompatible responses, but differed significantly from that of the mock control treatment, suggesting that WRKY68 may be involved in the bacterial blight response in rice. To further understand WRKY68’s roles in the resistance signaling pathway, WRKY68 recombinant protein was expressed in Escherichia coli and a microscale thermophoresis analysis was performed to investigate the interactions between WRKY68 and cis-elements in crucial pathogenesis-related (PR) genes. The results showed that the WRKY68 protein binds to W-boxes in the PR1b promoter region, with an apparent dissociation constant of 25 nmol L−1, while the binding between WRKY68 and PR10a was W-box independent. The results suggested that a possible modified form of the WRKY68 protein was induced during the interaction between rice and Xoo, which then regulated the activity of the downstream PR genes by binding with the W-boxes in the PR1b gene’s promoter region. Moreover, the constitutive transcription of the WRKY68 gene in dozens of rice tissues and the expression of the WRKY68 protein in leaves during all growth stages suggests that WRKY68 plays important roles in rice during normal growth processes.